2022
DOI: 10.1093/hmg/ddac170
|View full text |Cite
|
Sign up to set email alerts
|

A novel mouse model of CMT1B identifies hyperglycosylation as a new pathogenetic mechanism

Abstract: Mutations in the Myelin Protein Zero gene (MPZ), encoding P0, the major structural glycoprotein of peripheral nerve myelin, are the cause of Charcot–Marie-Tooth (CMT) type 1B neuropathy, and most P0 mutations appear to act through gain-of-function mechanisms. Here we investigated how misglycosylation, a pathomechanism encompassing several genetic disorders, may affect P0 function. Using in vitro assays, we showed that gain of glycosylation is more damaging for P0 trafficking and functionality as compared to lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Therefore, there may be a relationship between CMTDID disease and residue contact of these two positions. In addition, Veneri et al ( 21 ) found that the increase of glycosylation sites in MPZ can impair its function and lead to loosen myelin. Mutations in H49N produce an NCS sequence that belongs to the glycosylation motif (N-X-S/T), resulting in excessively glycosylation of MPZ.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there may be a relationship between CMTDID disease and residue contact of these two positions. In addition, Veneri et al ( 21 ) found that the increase of glycosylation sites in MPZ can impair its function and lead to loosen myelin. Mutations in H49N produce an NCS sequence that belongs to the glycosylation motif (N-X-S/T), resulting in excessively glycosylation of MPZ.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in vitro experiments have shown that the T124M mutation does not interfere with P0 adhesiveness [ 67 ]. Interestingly, the P0T124A and P0N122S mutations, which similarly abolish native N -glycosylation, are responsible for late-onset CMT1B with only moderate reduction of NCV [ 7 , 68 , 69 ], and like P0T124M, these mutated P0 proteins retain their adhesive propriety in vitro [ 70 ]. This suggests that the P0 protein backbone is generally sufficient for P0 homophilic adhesion and for myelin compaction.…”
Section: Discussionmentioning
confidence: 99%
“…Most Mpz protein mutants fail to reach the cell membrane or the myelin sheath and are instead accumulated in the ER, causing ER stress, stimulation of the unfolded protein response (UPR), hyperglycosylation, and apoptosis. [193][194][195][196][197][198][199][200] There are a great number of different Mpz mutations that cause a spectrum of phenotypes associated with CMT1B or CMT2 types. This variability raises the possibility that some Mpz mutations result in a gain of function while others result in a loss of function cellular effects; however, dominant-negative mechanisms are likely responsible in most cases.…”
Section: Gene Therapy Approaches For Cmt1bmentioning
confidence: 99%
“…Mpz is a major compact myelin transmembrane protein responsible for the proper compaction of myelin layers. Most Mpz protein mutants fail to reach the cell membrane or the myelin sheath and are instead accumulated in the ER, causing ER stress, stimulation of the unfolded protein response (UPR), hyperglycosylation, and apoptosis 193–200 . There are a great number of different Mpz mutations that cause a spectrum of phenotypes associated with CMT1B or CMT2 types.…”
Section: Gene Therapy Approaches For Specific Cmt Typesmentioning
confidence: 99%